The influences of radiation effects on DC/RF performances of Lg = 22 nm gate-all-around nanosheet field-effect transistor. (24th January 2022) - Ma, Yue; Bi, Jinshun; Majumdar, Sandip; Mehmood, Safdar; Ji, Lanlong; Sun, Yichao; Zhang, Chenrui; Fan, Linjie; Zhao, Biyao; Wang, Hanbin; Shen, Lizhi; Han, Tingting
Abstract: In this paper, we carried out detailed technology computer aided design simulations to investigate the radiation effects, e.g. total ionizing dose (TID) and single-event effects (SEEs), on direct current (DC) and radio frequency (RF) characteristics of the gate-all-around (GAA) nanosheet field-effect transistor (FET). The simulation model used is composed of seven-layer stacked GAA nanosheet FET with L g = 22 nm, which was implemented in this study. The open current and the drain-induced barrier lowering of the device are ∼3 mA μ m −1 and 47 mV V −1, respectively. The results indicate that the TID have little influence on the DC and RF characteristics when the transistor is working in an open state. During the SEEs simulation, we considered three incident directions for the high energy particle, including the lateral direction of the channels, the vertical direction of the channels and the top of the channels. The influence of the particle injecting along the lateral and vertical directions of the channels shows stronger relation with the distance from the incident point compared to the influence of the particle from the top. Besides, the general influence of the particle injecting along the lateral directions of the channels is higher than the other two directions. The total injected charge of the particle injecting along the lateral direction, along the vertical direction and from the top are 3 fC, 1.4 fC and 2.1 fC, respectively. As compared to the fin FET, the GAA nanosheet has superior RF performances and less sensitivity to TID effect. This work can provide a guideline for the GAA nanosheet devices in aerospace and avionic RF applications.